2018
DOI: 10.1136/bmjopen-2017-020478
|View full text |Cite
|
Sign up to set email alerts
|

Visual–motor integration and fine motor skills at 6½ years of age and associations with neonatal brain volumes in children born extremely preterm in Sweden: a population-based cohort study

Abstract: ObjectivesThis exploratory study aimed to investigate associations between neonatal brain volumes and visual–motor integration (VMI) and fine motor skills in children born extremely preterm (EPT) when they reached 6½ years of age.SettingProspective population-based cohort study in Stockholm, Sweden, during 3 years.ParticipantsAll children born before gestational age, 27 weeks, during 2004–2007 in Stockholm, without major morbidities and impairments, and who underwent MRI at term-equivalent age.Main outcome mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 57 publications
1
29
0
Order By: Relevance
“…An increasing body of research targeting the consequences of PT birth indicates cascading disruption to neurological development, [1][2][3][4][5][6] with the degree of deficits correlating with degree of prematurity. [7][8][9][10][11][12][13][14] Specifically, converging findings from animal models along with human neuroimaging investigations indicate that early disruption to white and gray matter development resulting from PT birth is largely responsible for inducing disruption of cognitive development [15][16][17][18][19] and psychopathologies. [20][21][22] Brain plasticity-the way experiences shape neural wiring of the brain-is thought to be one of the primary mechanisms through which humans adapt to environmental change and demonstrate resilience to adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing body of research targeting the consequences of PT birth indicates cascading disruption to neurological development, [1][2][3][4][5][6] with the degree of deficits correlating with degree of prematurity. [7][8][9][10][11][12][13][14] Specifically, converging findings from animal models along with human neuroimaging investigations indicate that early disruption to white and gray matter development resulting from PT birth is largely responsible for inducing disruption of cognitive development [15][16][17][18][19] and psychopathologies. [20][21][22] Brain plasticity-the way experiences shape neural wiring of the brain-is thought to be one of the primary mechanisms through which humans adapt to environmental change and demonstrate resilience to adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…A randomised controlled trial (RCT) showed preterm infants <33 weeks receiving a mean of 32 s DCC compared with a mean of ECC 6.6 s had better motor function at 18–22 months corrected age 9. In infants <27 weeks, areas of the brain responsible for visual motor integration and fine motor skills are known to be particularly vulnerable to injury, with resultant functional deficits noted 6.5 years later 10. Effective spontaneous ventilation for optimal cardiopulmonary transition in the majority of very preterm infants appears to occur more than a minute or two after birth; thus, timing is relevant to the physiology of transition.…”
mentioning
confidence: 99%
“…Specific brain volumes from TEA have been shown to prognosticate motor ability into late childhood. Volumes of the cerebellum and brainstem predicted fine motor skills at age six19 , and volumes of the frontal lobes, basal ganglia, thalamus, cerebellum, and brainstem were correlated with motor scores at age 1118 . Our results corroborate and extend prior studies by showing positive correlation between numerous subcortical volumes at TEA -the volume of the amygdala, brainstem, caudate, cerebellum, hippocampus, lentiform nuclei, subthalami nuclei, and thalamus-and motor outcomes at two-years corrected age.…”
mentioning
confidence: 91%
“…As such, researchers have turned to other structural brain features beyond overt injury. Brain volumes are consistently decreased in extremely-low-birth-weight or preterm cohorts [9][10][11][12][13][14] , and there is evidence that these volumetric changes prognosticate motor ability 13,[15][16][17][18][19][20][21] . Preterm infants also exhibit altered cortical morphometrics, including inner cortical curvature 22,23 , surface area 14,[22][23][24][25][26][27][28] , gyrification 14,23,[28][29][30] , and sulcal depth 14,23,28,29 at term.…”
Section: Introductionmentioning
confidence: 99%